Early stages in Bacillus subtilis transformation: association between homologous DNA and surface structures. - Garcia, E (1978)
The addition of ethylenediaminetetraacetate to competent cultures of Bacillus subtilis irreversibly inhibited the transformability as well as the cellular binding of DNA. Our results show that the inhibition of DNA binding by ethylenediaminetetraacetate in whole cells, protoplasts, and membrane vesicles is mainly due to a permanent alteration of the DNA receptors. Transformation absolutely requires free magnesium ions, whereas DNA binding is a magnesium-independent step. In contrast to ethylenediaminetetraacetate, the absence of Mg2+ does not irreversibly affect the capacity of the competent cells to be transformed DNA-binding receptors located at the cell surface remain associated with the plasma membrane after protoplasting and after isolation of membrane vesicles. A Mg2+-dependent endonucleolytic activity associated with the membrane appears to be responsible for the lower levels of binding by protoplasts in the presence of this ion.